Morphophysiological responses to drought in Ouratea fieldingiana (Gardner) Engl. (Ochnaceae), a species endemic to the semiarid savannas of Brazil - Matheus Lopes Souza; Renata Kécia de Oliveira; Ingrid H’Oara Carvalho Vaz da Silva; Rafaela Camargo Maia (Acta Botânica Brasílica, 2025)
Abstract Increased frequency and duration of droughts are projected due to climate change, with northeastern Brazil’s semi-arid region being one of the most affected globally. These changes in rainfall are expected to be particularly harmful to seedlings, impacting plant species’ population dynamics. We conducted a greenhouse experiment to assess how different water deficit levels affect the performance and morphophysiological responses of seedlings of Ouratea fieldingiana (Ochnaceae), a plant species endemic to the northeastern coast of Brazil. We hypothesized that higher water deficits would lead to significant reductions in seedling growth and alterations in morphophysiological traits. Overall, the seedlings demonstrated slow development, characterized by increased root allocation, fewer leaves, and a reduced leaf area ratio (LAR). Water stress further decreased growth, number of leaves, and relative water content (RWC%) while increasing floating leaf asymmetry (FLA). Furthermore, O. fieldingiana seedlings displayed limited capacity to acclimatize to very severe conditions, with all seedlings succumbing within the first 15 days. We conclude that severe water limitation may compromise the recruitment and survival of O. fieldingiana under prolonged drought scenarios, posing a significant risk to natural populations in the face of climate change.